Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Investigating the Effect of Tissue Size on Mycelial Growth of Seven Mushroom Species by Using a Novel Device for Precise Tissue Isolation - Sheng-Rong Liu; Wei-Rui Zhang; Ai-Ping Chen; Yun-Bo Kuang (Indian Journal of Microbiology, 2016)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Brain structure–function associations identified in large-scale neuroimaging data - Zhi Yang; Jiang Qiu; Peipei Wang; Rui Liu; Xi-Nian Zuo (Brain Structure and Function, 2016)

Adenovirus-mediated shRNA interference against HSV-1 replication in vitro - Bo Song; Xinjing Liu; Qingzhi Wang; Rui Zhang; Ting Yang; Zhiqiang Han; Yuming Xu (Journal of NeuroVirology, 2016)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

A new helvolic acid derivative from an endophytic Fusarium sp. of Ficus carica - Xi-Ai Liang; Yang-Min Ma; Hong-Chi Zhang; Rui Liu (Natural Product Research, 2016)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Synthesis and antifungal activity of dehydroabietic acid-based 1,3,4-thiadiazole-thiazolidinone compounds - Naiyuan Chen; Wengui Duan; Guishan Lin; Luzhi Liu; Rui Zhang; Dianpeng Li (Molecular Diversity, 2016)

Synthesis, Aggregation Induced Emission and Mechanochromic Luminescence of New β-Diketone Derivatives Bearing Tetraphenylene Moieties - Haijie Shi; Rui Liu; Senqiang Zhu; Qiqi Gong; Hong Shi; Xiaolin Zhu; Hongjun Zhu (Journal of Fluorescence, 2016)

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

The ROS derived mitochondrial respirstion not from NADPH oxidase plays key role in Celastrol against angiotensin II-mediated HepG2 cell proliferation - Xin Liu; Rui-wei Gao; Miao Li; Chun-feng Si; Yong-peng He; Min Wang; Ying Yang; Qing-yin Zheng; Chao-yun Wang (Apoptosis, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

New alkaloids from the leaves of Evodia rutaecarpa - Xiao Xia; Jian-Guang Luo; Rui-Huan Liu; Ming-Hua Yang; Ling-Yi Kong (Natural Product Research, 2016)

A field study on the dynamic uptake and transfer of heavy metals in Chinese cabbage and radish in weak alkaline soils - Shiwei Ai; Rui Guo; Bailin Liu; Liang Ren; Sajid Naeem; Wenya Zhang; Yingmei Zhang (Environmental Science and Pollution Research, 2016)

Increasing the recovery of heavy metal ions using two microbial fuel cells operating in parallel with no power output - Xiaohui Wang; Jing Li; Zhao Wang; Hairti Tursun; Rui Liu; Yanmei Gao; Yuan Li (Environmental Science and Pollution Research, 2016)

Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2016)
Abnormal angiogenesis is critical for portal hypertension in cirrhosis. Except for etiological treatment, no efficient medication or regime has been explored to treat the early stage of cirrhosis when angiogenesis is initiated or overwhelming. In this study, we explored an anti-angiogenesis effort through non-cytotoxic drugs octreotide and celecoxib to treat early stage of cirrhotic portal hypertension in an animal model. Peritoneal injection of thioacetamide (TAA) was employed to induce liver cirrhosis in rats. A combination treatment of celecoxib and octreotide was found to relieve liver fibrosis, portal venous pressure, micro-hepatic arterioportal fistulas, intrahepatic and splanchnic angiogenesis. Celecoxib and octreotide exerted their anti-angiogenesis effect via an axis of cyclooxygenase-2/prostaglandin E2/EP-2/somatostatin receptor-2, which consequently down-regulated phosphorylation of extracellular signal-regulated kinase (p-ERK)–hypoxia-inducible factor-1α (HIF-1α)–vascular endothelial growth factor (VEGF) integrated signaling pathways. In conclusions, combination of celecoxib and octreotide synergistically ameliorated liver fibrosis and portal hypertension of the cirrhotic rats induced by TAA via the inhibition of intrahepatic and extrahepatic angiogenesis. The potential mechanisms behind the regimen may due to the inactivation of p-ERK–HIF-1α–VEGF signaling pathway.

Stiffness optimisation of coupled shear wall structure by modified genetic algorithm - Tao Dai; Xing Liu; Rui Gao (European Journal of Environmental and Civil Engineering, 2016)

Expression Profile of MiR-128 in the Astrocytoma Patients and Cell Lines - Jingjing Xu; Yuqiong Liu; Si Guo; Shengli Ma; Lin Xiao; Na Wei; Rui Xue (Molecular Neurobiology, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Using isotopic, hydrogeochemical-tracer and temperature data to characterize recharge and flow paths in a complex karst groundwater flow system in northern China - Ziyong Sun; Rui Ma; Yanxin Wang; Teng Ma; Yunde Liu (Hydrogeology Journal, 2016)

Acute toxicity and chemical evaluation of coking wastewater under biological and advanced physicochemical treatment processes - Ma Dehua; Liu Cong; Zhu Xiaobiao; Liu Rui; Chen Lujun (Environmental Science and Pollution Research, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

Genomewide analysis of the lateral organ boundaries domain gene family in Vitis vinifera - HUI CAO; CAI-YUN LIU; CHUN-XIANG LIU; YUE-LING ZHAO; RUI-RUI XU (Journal of Genetics, 2016)

Assessing spatial likelihood of flooding hazard using naïve Bayes and GIS: a case study in Bowen Basin, Australia - Rui Liu; Yun Chen; Jianping Wu; Lei Gao; Damian Barrett; Tingbao Xu; Linyi Li; Chang Huang; Jia Yu (Stochastic Environmental Research and Risk Assessment, 2016)

Prehistoric agriculture development in the Yunnan-Guizhou Plateau, southwest China: Archaeobotanical evidence - HaiMing Li; XinXin Zuo; LiHong Kang; LeLe Ren; FengWen Liu; HongGao Liu; NaiMeng Zhang; Rui Min; Xu Liu; GuangHui Dong (Science China Earth Sciences, 2016)

A Method for Dynamic Risk Assessment and Management of Rockbursts in Drill and Blast Tunnels - Guo-Feng Liu; Xia-Ting Feng; Guang-Liang Feng; Bing-Rui Chen; Dong-Fang Chen; Shu-Qian Duan (Rock Mechanics and Rock Engineering, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Cloning and characterizing of the murine IRF-3 gene promoter region - Hua-Guo Xu; Lifei Liu; Shan Gao; Rui Jin; Wei Ren; Guo-Ping Zhou (Immunologic Research, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Selenium Deficiency Attenuates Chicken Duodenal Mucosal Immunity via Activation of the NF-κb Signaling Pathway - Zhe Liu; Yanpeng Qu; Jianfa Wang; Rui Wu (Biological Trace Element Research, 2016)

Tigecycline: Alone or in combination? - Yun Cai; Nan Bai; Xu Liu; Beibei Liang; Jin Wang; Rui Wang (Infectious Diseases, 2016)

Dietary exposure to lead of adults in Shenzhen city, China - Liubo Pan; Zhou Wang; Zhaoqiong Peng; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Nimal Pathiraja; Ying Xiao; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Serum CXCL12 Levels as a Novel Predictor of Future Stroke Recurrence in Patients with Acute Ischemic Stroke - Xiao-Lin Gu; Lin Liu; Xiang-Dong Lu; Zhen-Rui Liu (Molecular Neurobiology, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Comparison of high-rate GPS, strong-motion records and their joint use for earthquake monitoring: a case study of the 2011 Mw 9.0 Tohoku earthquake - Rui Tu; Pengfei Zhang; Rui Zhang; Jinhai Liu (Arabian Journal of Geosciences, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Re: “PICALM Gene rs3851179 Polymorphism Contributes to Alzheimer’s Disease in an Asian Population” - Ming-Jie Wang; Rui-Ping Liu; Zhi-Jun Kong (NeuroMolecular Medicine, 2016)

SAR Image Change Detection Method Based on Pulse-Coupled Neural Network - Rui Liu; Zhenhong Jia; Xizhong Qin; Jie Yang; Nikola Kasabov (Journal of the Indian Society of Remote Sensing, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Construction of a bivalent DNA vaccine co-expressing S genes of transmissible gastroenteritis virus and porcine epidemic diarrhea virus delivered by attenuated Salmonella typhimurium - Yudi Zhang; Xiaohui Zhang; Xiaodan Liao; Xiaobo Huang; Sanjie Cao; Xintian Wen; Yiping Wen; Rui Wu; Wumei Liu (Virus Genes, 2016)

The role of exogenous electron donors for accelerating 2,4,6-trichlorophenol biotransformation and mineralization - Ning Yan; Rongjie Li; Hua Xu; Ling Li; Lihui Yang; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

Phylogenetic analysis reveals that Japanese encephalitis virus genotype III is still prevalent in swine herds in Sichuan province in China - Rui Wu; Qiao Wang; Hongming Liu; Chunxia Chai; Bo He; Xiaobo Huang; Yiping Wen; Xintian Wen; Qiguai Yan; Xiaoping Ma; Sanjie Cao (Archives of Virology, 2016)

A new triterpenoid saponin from Clinopodium chinense (Benth.) O. Kuntze - Biao Zeng; Guang-Da Liu; Bao-Bao Zhang; Shan-shan Wang; Rui Ma; Bei-Shan Zhong; Bai-qiu He; Yan Liang; Fei-Hua Wu (Natural Product Research, 2016)

Current approaches to reduce or eliminate mitochondrial DNA mutations - Liang Yang; Tingfang Mei; Xiaobing Lin; Haite Tang; Yi Wu; Rui Wang; Jinglei Liu; Zahir Shah; Xingguo Liu (Science China Life Sciences, 2016)

Exogenous application of ABA mimic 1 (AM1) improves cold stress tolerance in bermudagrass (Cynodon dactylon) - Zhangmin Cheng; Rui Jin; Minjie Cao; Xiaodong Liu; Zhulong Chan (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

A mutation in SLC22A4 encoding an organic cation transporter expressed in the cochlea strial endothelium causes human recessive non-syndromic hearing loss DFNB60 - Mariem Ben Said; M’hamed Grati; Takahiro Ishimoto; Bing Zou; Imen Chakchouk; Qi Ma; Qi Yao; Bouthaina Hammami; Denise Yan; Rahul Mittal; Noritaka Nakamichi; Abdelmonem Ghorbel; et al. (Human Genetics, 2016)

Optimization of operation conditions for the mitigation of nitrous oxide (N2O) emissions from aerobic nitrifying granular sludge system - Rui-Ting Liu; Xin-Hua Wang; Yan Zhang; Ming-Yu Wang; Ming-Ming Gao; Shu-Guang Wang (Environmental Science and Pollution Research, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Plasma miR-221/222 Family as Novel Descriptive and Prognostic Biomarkers for Glioma - Rui Zhang; Bo Pang; Tao Xin; Hua Guo; Yi Xing; Shangchen Xu; Bin Feng; Bin Liu; Qi Pang (Molecular Neurobiology, 2016)

Evaluation of a water-soluble adjuvant for the development of monoclonal antibodies against small-molecule compounds - Rui Liu; Ying Liu; Mei-jing Lan; Niusha Taheri; Jing-li Cheng; Yi-rong Guo; Guo-nian Zhu (Journal of Zhejiang University-SCIENCE B, 2016)

Immunogenicity of transmissible gastroenteritis virus (TGEV) M gene delivered by attenuated Salmonella typhimurium in mice - Ying Qing; Jiawen Liu; Xiaobo Huang; Yaqing Li; Yudi Zhang; Jie Chen; Xintian Wen; Sanjie cao; Yiping Wen; Rui Wu; Qigui Yan; Xiaoping Ma (Virus Genes, 2016)

The influence of geological movements on the population differentiation of Biston panterinaria (Lepidoptera: Geometridae) - Rui Cheng; Nan Jiang; Xiushuai Yang; Dayong Xue; Shuxian Liu; Hongxiang Han (Journal of Biogeography, 2016)
Aim East Asia is known for its exceptionally high levels of biodiversity, which is connected to its high level of species differentiation. Geological movements are the most important factor promoting the species differentiation in East Asia. In this paper, we choose Biston panterinaria , a moth species widely distributed in East Asia, to study the relative contributions of geographical isolation and glaciation cycles to its current genetic constitution. Location East Asia. Methods Phylogenetic analyses were based on three data sets. beast was used to estimate the divergence time and reconstruct the maximum clade credibility tree. Mismatch distribution and Bayesian skyline plots ( BSP ) were used to infer historical population fluctuations. maxent was used to predict the potential species distributions during two periods: the present day and the Last Glacial Maximum ( LGM ). Results The phylogenetic tree and the median joining network strongly supported four reciprocally monophyletic lineages: northern, Yunnan‐Tibet, southern and Yunnan‐ SE . The estimates of divergence time suggested that three differentiation processes occurred at approximately 1.17, 0.76 and 0.67 Ma. Within the northern and southern lineages, lineage divergence occurred at approximately 0.17 and 0.16 Ma. Mismatch distribution and BSP suggested that the northern and southern lineages experienced one expansion after the LGM , and this result was consistent with the result of the ecological niche model. Main conclusions Our results suggested that B. panterinaria experienced three fragmentations of wide‐ranging ancestral populations, and that mountain barrier isolation induced by geological movements is the main driver of lineage differentiation. Climatic oscillations during the Pleistocene affected the population differentiation within both the northern and southern lineages. The distribution of the four lineages of B. panterinaria is generally consistent with the zoogeographical regionalization of China. This study provides direct evidence for the importance of mountain barriers in promoting population differentiation.

Global transcriptome profiling analysis reveals insight into saliva-responsive genes in alfalfa - Wenxian Liu; Zhengshe Zhang; Shuangyan Chen; Lichao Ma; Hucheng Wang; Rui Dong; Yanrong Wang; Zhipeng Liu (Plant Cell Reports, 2016)

Mutations in circularly permuted GTPase family genes AtNOA1/RIF1/SVR10 and BPG2 suppress var2-mediated leaf variegation in Arabidopsis thaliana - Yafei Qi; Jun Zhao; Rui An; Juan Zhang; Shuang Liang; Jingxia Shao; Xiayan Liu; Lijun An; Fei Yu (Photosynthesis Research, 2016)

Determinants of the biodiversity patterns of ammonia-oxidizing archaea community in two contrasting forest stands - Jie Chen; Yichao Rui; Xuan Zhou; Wanhui Ye; Wei Liu (Journal of Soils and Sediments, 2016)

Arbuscular Mycorrhizal Fungus Alleviates Chilling Stress by Boosting Redox Poise and Antioxidant Potential of Tomato Seedlings - Airong Liu; Shuangchen Chen; Mengmeng Wang; Dilin Liu; Rui Chang; Zhonghong Wang; Xiaomin Lin; Bing Bai; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2016)

Synthesis, Luminescent Properties of aza-Boron-Diquinomethene Difluoride Complexes and Their Application for Fluorescent Security Inks - Long Gu; Rui Liu; Hong Shi; Qiang Wang; Guangliang Song; Xiaolin Zhu; Shidong Yuan; Hongjun Zhu (Journal of Fluorescence, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Bovine lactotroph cultures for the study of prolactin synthesis functions - Jianfa Wang; Zhanqing Yang; Shoupeng Fu; Bingrun Liu; Dianjun Wu; Wei Wang; Dongbo Sun; Rui Wu; Juxiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.

Variation analysis of pathogenic Vibrio spp. and Pseudomonas spp. in Changhai mollusc farming waters using real-time PCR assay during 2011–2014 - Rui Liu; Limei Qiu; Xin Zhao; Huan Zhang; Lingling Wang; Zhanhui Hou; Dahai Gao; Linsheng Song (Marine Biology Research, 2016)

Change of Polysaccharide Content and Its Relation with Nitrogen Level in Sugarcane Leaves Under Nitrogen-Fixing Bacteria Inoculation and Nitrogen Supply - Xi-Hui Liu; Hui-Ping Ou; Rong-Zhong Yang; Rong-Hua Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

UV photolysis for enhanced phenol biodegradation in the presence of 2,4,6-trichlorophenol (TCP) - Jiaxiu Song; Wenbing Wang; Rongjie Li; Jun Zhu; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

Geological and geochronological constraints on the genesis of the giant Tongkuangyu Cu deposit (Palaeoproterozoic), North China Craton - Xuan Liu; Hong-Rui Fan; M. Santosh; Kui-Feng Yang; Zheng-Jie Qiu; Fang-Fang Hu; Bo-Jie Wen (International Geology Review, 2016)

A new isoflavanone from the trunk of Horsfieldia pandurifolia - Qin Ma; Yujiao Liu; Rui Zhan; Yegao Chen (Natural Product Research, 2016)

Uncertainty-Based Multi-Objective Decision Making with Hierarchical Reliability Analysis Under Water Resources and Environmental Constraints - Feifei Dong; Yong Liu; Han Su; Zhongyao Liang; Rui Zou; Huaicheng Guo (Water Resources Management, 2016)

Timing of uplift and evolution of the Lüliang Mountains, North China Craton - JunFeng Zhao; ChiYang Liu; Nigel Mountney; JianJun Lu; JiLong Cao; Yao Yang; Rui Xue (Science China Earth Sciences, 2016)

ISRM Suggested Method for In Situ Microseismic Monitoring of the Fracturing Process in Rock Masses - Ya-Xun Xiao; Xia-Ting Feng; John A. Hudson; Bing-Rui Chen; Guang-Liang Feng; Jian-Po Liu (Rock Mechanics and Rock Engineering, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

A Study of 2,3,7,8-Tetrachlorodibenzo-p-dioxin Induced Liver Injury in Jian Carp (Cyprinus carpio var. Jian) Using Precision-Cut Liver Slices - Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Rui Jia; Guo-Jun Yin (Bulletin of Environmental Contamination and Toxicology, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

A cycle slip fixing method with GPS + GLONASS observations in real-time kinematic PPP - Shirong Ye; Yanyan Liu; Weiwei Song; Yidong Lou; Wenting Yi; Rui Zhang; Peng Jiang; Yu Xiang (GPS Solutions, 2016)

Role of CSL-dependent and independent Notch signaling pathways in cell apoptosis - Chong Zeng; Rui Xing; Jing Liu; Feiyue Xing (Apoptosis, 2016)